Digital Internal Controls: Safeguarding Data Integrity and Compliance in a Technologically Evolving Landscape - Suhardjo, Suhardjo; Suharti, Suharti; Suyono, Suyono; Mukhsin, Mukhsin; Hadi, Syukri (International Conference on Business Management and Accounting, 2023)
Digital Internal Control (DIC) refers to the procedures and systems employed by organizations to manage risks and uphold the integrity of financial and operational information within a digital framework. As reliance on digital technologies grows, the need for effective internal control systems has become more pressing to combat fraud, ensure data accuracy, and comply with regulatory standards. This research investigates the components, effectiveness, and challenges associated with DIC systems. It highlights key elements such as access controls, data encryption, audit trails, and automated monitoring, and evaluates their role in risk mitigation and compliance assurance. The study also explores common challenges, including the high costs and complexity of implementation, particularly for smaller organizations, and the necessity for continuous updates and training due to rapid technological advancements. Findings suggest that robust DIC systems significantly reduce incidents of data breaches and fraud, with automated monitoring and audit trails being particularly effective for early detection of irregularities. To enhance DIC systems, the research recommends investing in advanced technologies, conducting regular training and audits, and developing comprehensive policies. This research aims to provide insights into creating a secure and resilient digital environment that supports organizational integrity and regulatory compliance.